The Implementation of the CTL (Contextual Teaching and Learning) Instructional Strategy to Improve the Learning Outcomes of Grade XI Students of the Motorcycle Engineering Department in the Engine Systems Subject at SMK Negeri 12 Malang - Rafi Krisna Arisandy Dika Ragil Fahrezy; Syarif Suhartadi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to improve the learning outcomes of Grade XI students of the Motorcycle Engineering Department in the Engine Systems subject through the implementation of the Contextual Teaching and Learning (CTL) instructional strategy. This study used a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages, involving 32 students of Grade XI Motorcycle Engineering Department at SMK Negeri 12 Malang. Data were collected through learning outcome tests in the form of pretests and posttests, as well as observation sheets for student and teacher activities, and analyzed using descriptive quantitative and qualitative techniques. The results showed that CTL significantly improved students' learning outcomes, with average scores in Cycle I increasing from 66.75 to 83.94, and in Cycle II from 75.06 to 88.25. This strategy also enhanced student participation, learning engagement, and the ability to relate Engine Systems concepts to real-life situations and the automotive industry context. It was concluded that CTL is effective in improving learning outcomes and the quality of the learning process in vocational education, particularly in the Engine Systems subject.